Issuing the Locality in English Textbooks Produced by Indonesian Islamic Institution - Zulfi Zumala Dwi Andriani; Ahmad Mufarih Hasan Fadly (Nazhruna: Jurnal Pendidikan Islam, 2025)
The discussions of English textbooks are dominantly only concerned with the product, value and representation of textbooks without giving intention to the production process. This present study discusses the production process of English textbooks produced by Indonesia Islamic Institution (Pesantren MS) and the content of English textbooks. This research adopts a qualitative method; primary data were gathered through in-depth interviews with some interviewees, the Pesantren leader, and the authors of the books to get information about the production process and the materials selected for the textbook. Furthermore, the data were also gathered from the content of six English textbooks, which were scrutinized based on Pesantren elements. The research findings demonstrate that the production of the textbooks was based on two reasons, namely Pesantren's interest and the teacher's interest in providing English materials and curriculum for English language teaching in Pesantren. However, the content of the textbook was still lacking in representing Pesantren content; only four items were found, namely pictures of Kyai (Pesantren leader), mosques, the teaching of classical books and student activities. Moreover, in enhancing intercultural communication among students, the study suggested creatively negotiating the locality interest in the English learning process through content integration in teaching materials and textbooks, teaching methodology, and adjustment of the curriculum in Pesantren. Furthermore, analyzing the English textbook produced by Pesantren MS aims to propel Pesantren towards better negotiating, integrating, and contributing of English textbook in the development of English teaching and learning and its curriculum among Pesantren.